Comparison of manual and automated AmpliSeq™ workflows in the typing of a Somali population with the Precision ID Identity Panel. (November 2017) - van der Heijden, Suzanne; de Oliveira, Susanne Juel; Kampmann, Marie-Louise; Børsting, Claus; Morling, Niels
Highlights: Automated and manual AmpliSeq workflows were compared. Complete concordance between genotypes obtained with manual and automated workflows. The applicability of the previously selected SNP analysis criteria was corroborated. Ion Chef™/Ion S5™ workflow gave the best results and required least hands-on time. Somali HID-SNP database was generated. Abstract: The Precision ID Identity Panel was used to type 109 Somali individuals in order to obtain allele frequencies for the Somali population. These frequencies were used to establish a Somali HID-SNP database, which will be used for the biostatistic calculations in family and immigration cases. Genotypes obtained with the Precision ID Identity Panel were found to be almost in complete concordance with genotypes obtained with the SNP for ID PCR-SBE-CE assay. In seven SNP loci, silent alleles were identified, of which most were previously described in the literature. The project also set out to compare different AmpliSeq™ workflows to investigate the possibility of using automated library building in forensic genetic case work. In order to do so, the SNP typing of the Somalis was performed using three different workflows: 1) manual library building and sequencing on the Ion PGM™, 2) automated library building using the Biomek ® 3000 and sequencing on the Ion PGM™, and 3) automated library building using the Ion Chef™ and sequencing on the Ion S5™. AmpliSeq™ workflows were compared based on coverage, locus balance, noise, and heterozygote balance. Overall, the Ion Chef™/Ion S5™ workflow was found to give the best results and required least hands-on time in the laboratory. However, the Ion Chef™/Ion S5™ workflow was also the most expensive. The number of libraries that may be constructed in one Ion Chef™ library building run was limited to eight, which is too little for high throughput workflows. The Biomek ® 3000/Ion PGM™ workflow was found to perform similarly to the manual/Ion PGM™ workflow. This argues for the use of automated library building in forensic genetic case work. Automated library building decreases the workload of the laboratory staff, decreases the risk of pipetting errors, and simplifies the daily workflow in forensic genetic laboratories.